The Use of Mnemonic Technique to Increase Vocabulary Mastery of Students - Nur Aisyah Safri; Patahuddin (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2019)
This research was intended to reveal that: can mnemonic technique increase vocabulary mastery of the eight grade students of SMP Negeri 3 Suppa Pinrang significantly. This research used Quasi Experimental method, with two class pre-test and post-test design. The population was the eight grade students of SMP Negeri 3 Suppa Pinrang. The samples were drawn by using nonequivalent group design that consisted of 40 students which were class VIII, A as experimental class, VIII, C as the control class. The data were acquired by using vocabulary test. The vocabulary mastery test was applied in the pre-test and post-test. The data required from reading test was analyzed by using t-test and percentage technique. The result of the data analyzed shows that mnemonic technique can increase vocabulary mastery of the eight grade students of SMP Negeri 3 Suppa Pinrang significantly. It was proved by the mean score of the pre-test was (38.94) and the post-test was (82.10). It showed that used of mnemonic technique can increase vocabulary mastery of the eight grade students of SMP Negeri 3 Suppa Pinrang significantly. After analyzing the data by the t-test formula, the result of t-test value in post-test was (4.83) and t-table value was (2.024). Those indicated that H1 was accepted and H0 was rejected. The students who were taught through mnemonic technique were better than the students who were taught words list technique.